Amino acid, mineral, and degree of hydrolysis of vinegar-egg and its lipid lowering and antioxidant effects in vitro and in vivo - Zheng, Yue; Liu, Kun; Yan, Wanghui; Wei, Guohua; Chao, Xinyu; Yan, Xiang; Zeng, Qingmei (Penerbit Universiti Kebangsaan Malaysia, 2019)
Vinegar-egg, a product derived from vinegar and eggs, is a healthy beverage that has been popular in China for a long time. It contains abundant essential and hydrophobic amino acids, and minerals especially Ca and Mg via chemical analyses. The results showed changes of degree of hydrolysis (DH) by different soaking time. In vitro, vinegar-egg showed higher bile acid binding capacity and exhibited inhibition percentages of cholesterol micellar solubility. The DPPH radical-scavenging activity and lipid peroxidation inhibitory activity of vinegar-egg were evaluated, respectively. Additionally, after a 11-week experiment in vivo, high-fat diet (HFD) fed mice had higher weight gains, adipose tissue (EAT and SAT) and serum/liver lipids than the standard chow diet (SCD) fed ones, but vinegar-egg supplementation decreased (p < 0.05) them which may resulted in hyperlipidemia. Serum alanine aminotransferase (ALT) value and aspartate aminotransferase (AST) value in HFD-fed mice were reduced (p < 0.05) by supplementing vinegar-egg due to decreased (p < 0.05) malonaldehyde (MDA) levels, increased superoxide dismutase (SOD) and glutathione peroxidase (GPH-Px) activities. Compared with those fed the SCD, HFD induced extensive intrahepatic lipid droplets and hepatic necrosis. However, supplementing the HFD with vinegar-egg attenuated these anomalies in a dose-dependent manner. Taken together, the component profiles of vinegar-egg contributed the lipid lowering and antioxidant effects on HFD-fed mice. Hence, vinegar-egg is expected to be a useful ingredient in physiologically functional foods for the treatment of hyperlipidemia.